Study on foam freeze drying in vaccine - ZHANG Shaozhi; SHI Mingyao; CHEN Guangming; LYU Fang; LU Yu (浙江大学学报. 农业与生命科学版)
Freeze-drying has been widely used in the production of pharmaceuticals, vaccines and high-valued foods. Foam freeze-drying is a new type of drying technology, in which the sample is foamed and frozen before drying. Compared with traditional freeze-drying method, the new method can reduce operation time and cost significantly. Some foreign researchers have used this method to produce heat-resistant vaccines which can endure higher temperature and remain effective after a longer storage in refrigerator. Up to now, little research about foam freeze-drying has been reported domestically. In this study, newcastle disease vaccine was used as an example to illustrate the procedure of foam freeze-drying method and to test its capability of producing heat-resistant vaccine.The ingredient of the foam freeze drying (FFD) sample included w (trehalose)=10%, w (hydrolyzed gelatin)=5%, w(pluronic F-108)=3%, w(arginine)=2%, 25 mmol/L phosphate buffer (pH=7.2). The sample was prepared through the following procedure: 1) One milliliter sample was placed on the plate of the freeze dryer and cooled to 15 ℃; 2) then the pressure was lowered to 5 Pa and foaming began; 3) after one hour the plate temperature was increased up to 31℃ at a velocity of 0.7 ℃/min and kept for another 48 hours. The samples made by foam freeze drying were analyzed with thermal analysis and aging test, and were compared with live attenuated samples and heat-resistant samples prepared by traditional freeze drying. The latter two kinds of sample were bought from market (Tianbang Biotechnology Corporation, Nanjing, China). Thermal analysis was done with a differential scanning calorimetry (DSC 200 F3 Maia, NETZSCH, Germany). The procedure was as follows: 1) the sample was cooled to —20℃ at a rate of 10 ℃/min and held for 3 minutes; 2) the sample was heated to 80℃ at the rate of 10 ℃/min and held for 3 minutes; 3) the sample was cooled to room temperature at the rate of 10 ℃/min. Aging test was carried out by placing the sample at 37℃ for 10 days and thereafter measuring its EID50. EID50 was determined by vaccination with chick embryo and Reed-Muench calculation method.The appearance of the FFD sample was like sponge, totally different from the flat biscuit-like sample made by traditional freeze drying method. The average glass transition temperature of FFD vaccine was 33.9 ℃, higher than 30.2℃ of live attenuated vaccine, but lower than 40.1℃ of heat-resistant vaccine. This means that the heat resistance ability of FFD vaccine is physically better than that of live attenuated vaccine. After aging test the titers decreased for FFD vaccine was 1.1, which was a little higher than 0.8 for heat-resistant vaccine. The latter result was in consistent with the former result.It is clear that FFD vaccine has its own superiority on heat resistance ability, although the formula and operation parameters still need to be improved. Considering its obvious economic prospect, it is worth to carry out further work on the study of FFD vaccine.